Metabolic Control of Tobacco Pollination by Sugars and Invertases. Issue 2 (6th December 2016) - Goetz, Marc; Guivarćh, Anne; Hirsche, Jörg; Bauerfeind, Martin Andreas; González, María-Cruz; Hyun, Tae Kyung; Eom, Seung Hee; Chriqui, Dominique; Engelke, Thomas; Großkinsky, Dominik K.; Roitsch, Thomas
Abstract : Invertases and hexose transporters, as essential components of carbohydrate supply, are regulated in a spatiotemporally coordinated manner to maintain functionality of tobacco pollination. Abstract: Pollination in flowering plants is initiated by germination of pollen grains on stigmas followed by fast growth of pollen tubes representing highly energy-consuming processes. The symplastic isolation of pollen grains and tubes requires import of Suc available in the apoplast. We show that the functional coupling of Suc cleavage by invertases and uptake of the released hexoses by monosaccharide transporters are critical for pollination in tobacco ( Nicotiana tabacum ). Transcript profiling, in situ hybridization, and immunolocalization of extracellular invertases and two monosaccharide transporters in vitro and in vivo support the functional coupling in supplying carbohydrates for pollen germination and tube growth evidenced by spatiotemporally coordinated expression. Detection of vacuolar invertases in maternal tissues by these approaches revealed metabolic cross talk between male and female tissues and supported the requirement for carbohydrate supply in transmitting tissue during pollination. Tissue-specific expression of an invertase inhibitor and addition of the chemical invertase inhibitor miglitol strongly reduced extracellular invertase activity and impaired pollen germination. Measurements of (competitive) uptake of labeled sugars identified two import pathways for exogenously available Suc into the germinating pollen operating in parallel: direct Suc uptake and via the hexoses after cleavage by extracellular invertase. Reduction of extracellular invertase activity in pollen decreases Suc uptake and severely compromises pollen germination. We further demonstrate that Glc as sole carbon source is sufficient for pollen germination, whereas Suc is supporting tube growth, revealing an important regulatory role of both the invertase substrate and products contributing to a potential metabolic and signaling-based multilayer regulation of pollination by carbohydrates.